Protein transduction domain-mediated influenza NP subunit vaccine generates a potent immune response and protection against influenza virus in mice - Yuan Yin; BeiBei Li; Linting Zhou; Jian Luo; Xueying Liu; Shilei Wang; Qun Lu; Wensong Tan; Ze Chen (Emerging Microbes and Infections)
The nucleoprotein (NP) is a highly conserved internal protein of the influenza virus, a major target for universal influenza vaccine. Our previous studies have proven NP-based subunit vaccine can provide partial protection in mice. It is reported that the protein transduction domain (PTD) TAT protein from human immunodeficiency virus-1 (HIV-1) is able to penetrate cells when added exogenous protein and could effectively enhance the immune response induced by the exogenous protein. In present study, the recombinant protein TAT-NP, a fusion of TAT and NP was effectively expressed in Escherichia coli and purified as a candidate component for an influenza vaccine. We evaluated the immunogenicity and protective efficacy of recombinant influenza TAT-NP vaccine by intranasal immunization. In vitro experiments showed that TAT-NP could efficiently penetrate into cells. Animal results showed that mice vaccinated with TAT-NP could not only induce higher levels of IgG and mucosal IgA, but also elicit a robust cellular immune response. Moreover, the TAT-NP fusion protein could significantly increase the protection of mice against lethal doses of homologous influenza virus PR8 and could also provide mice protection against a lethal dose challenge against heterosubtypic H9N2 and H3N2 influenza virus. In conclusion, the recombinant TAT-NP might be a universal vaccine candidate against influenza virus.